Reformpædagogik, før nu og fremtiden - Nørgaard, Ellen (Psyke & Logos, 2023)
New education was introduced in Denmark in the twenties. Periodicals were published, organizations established and experimental classes started. The most important were the classes at Vanloese School in Copenhagen. Here the children had freedom of movement at speech and the curriculum was developed from a Montessori inspired teaching material and the experiences and ideas of the children. The classes functioned well, but after four years they were closed down by the school board of Copenhagen. At the same time New education was transformed into a programme of reforms. Co-education, introduction of creative arts and abolition of corporal punishment are examples of this programme. As the programme was worded and the political work started, the dream of New education faded. Nevertheless central concepts have survived and are now elements in progressive teaching. Progressivism of today protects the child as did New education and that is what progressivism always have done. The question therefore arises whether there still is and always have been a tension between the claims of the school and children's human development? If this tension is constant New education should not be regarded as a criticism of past authoritarian times, but as a manifestation of a still vivid and constant criticism of Western civilization.